Modern application and prospects of the stable isotopes method for studying avian influenza A virus transmission in migratory birds - O. R. Druzyaka; A. V. Druzyaka; M. A. Gulyaeva; F. Huettmann; A. M. Shestopalov (Юг России: экология, развитие, 2019)
Aim. The circulation and transmission of pathogens is a global biological phenomenon that is closely associated with bird migration. This analysis was carried out with  the aim of understanding and assessing the prospects of using the stable isotope  method to study the circulation and transmission of the avian influenza A virus via  migratory birds. Discussion. Insufficient data on the distances of migration of infected birds and their  interpopulational relationships leaves open the question of the transmission of highly pathogenic influenza viruses (HSV) in the wild bird population. A deeper study of  the role of migrations in the spread of HSV may possibly allow the more effective  investigation of the transmission of the viral pathogen between individuals at migration stopover sites and the clarification of global migration routes. New methodological approaches are providing a more complete picture of the geography and phenology of migrations, as well as of the consequences of migratory behavior for species biology. The study of the quantitative component of migratory flows based on  the analysis of the content of stable isotopes (SIMS) in bird tissues seems very promising. This method is being applied to the solution of various environmental issues,  including the study of animal migrations.   Conclusion. Based on data from the scientific literature, it is shown that SIMS is  promising for the clarification of bird migration routes and the quantification of their  intensity. The resolving power of the method is sufficient to determine the migration  pathways of carriers of viral pathogens on the scale of zoogeographic subdomains  and in even further detail. However, to date, there have been few such studies: in  Russia they have not been conducted at all. The increased use of the SIMS methodology may possibly reveal new ways in which viral infections are spread via birds.